2012
DOI: 10.5402/2012/904963
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Intracanal Medications Based on Calcium Hydroxide

Abstract: Objective. The aim of this study was to evaluate the rat subcutaneous tissue reaction to calcium hydroxide-based intracanal medicaments, UltraCal XS (calcium hydroxide, barium sulphate, aqueous matrix), Hydropast (calcium hydroxide, barium sulphate, and propyleneglycol), and Calen (Calcium hydroxide, zinc oxide, colophony, and polyethyleneglycol), used as a control. Methods. Forty-eight rats (Rattus Norvegicus Holtzman) were distributed in three groups: Calen, UltraCal XS, and Hydropast. Polyethylene tubes fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 30 publications
3
19
1
6
Order By: Relevance
“…Calcium hydroxide is widely 48,[405][406][407][408][409][410][411][412][413][414][415][416]2015 used in dentistry due to its biocompatible properties and antimicrobial, anti-inflammatory and reparative activities (Hauman & Love 2003a,b, Mohammadi & Dummer 2011, de Sousa et al 2011, Gondim et al 2012. The biocompatibility results obtained in this study for calcium hydroxide paste are consistent with those reported by several authors (Holland et al 2001, Semenoff et al 2008, Silva et al 2010, Andolfatto et al 2012).…”
Section: ) Empty Tubesupporting
confidence: 89%
“…Calcium hydroxide is widely 48,[405][406][407][408][409][410][411][412][413][414][415][416]2015 used in dentistry due to its biocompatible properties and antimicrobial, anti-inflammatory and reparative activities (Hauman & Love 2003a,b, Mohammadi & Dummer 2011, de Sousa et al 2011, Gondim et al 2012. The biocompatibility results obtained in this study for calcium hydroxide paste are consistent with those reported by several authors (Holland et al 2001, Semenoff et al 2008, Silva et al 2010, Andolfatto et al 2012).…”
Section: ) Empty Tubesupporting
confidence: 89%
“…UltraCal XS, Hydropast and Calen paste also provided tissue compatibility (Andolfatto et al . ). Thus, calcium hydroxide‐based pastes may be considered suitable for clinical use in pulp therapy, mainly for teeth with periapical lesions.…”
Section: Discussionmentioning
confidence: 97%
“…MOs are outstanding by the capacity to ingest and process foreign materials and by acting in the release of chemokines, responsible for the recruitment of inflammatory cells (Ibraguimov, Owens, Su, & Tang, ; Kochanowski et al, ; Yamanaka et al, ). Furthermore, they may fuse and originate MGCs, which are capable of potentiating the proinflammatory response and help in limitation and removal of residues considered non‐inert to the body (Andolfatto et al, ; Costa, Ribeiro, Giro, Randall, & Hebling, ).…”
Section: Introductionmentioning
confidence: 99%